The Effects of Light Intensity and Flow Speed on Biogeochemical Variability Within a Fringing Coral Reef in Onna‐Son, Okinawa, Japan. Issue 12 (7th December 2022) - Rintoul, M. S.; Courtney, T. A.; Dohner, J. L.; Giddings, S. N.; Kekuewa, S. A. H.; Mitarai, S.; Monismith, S. G.; Pezner, A. K.; Andersson, A. J.
Abstract: Global warming and ocean acidification are driving declines in seawater dissolved oxygen (DO) concentrations and pH. Predicting how these changes will affect shallow, near‐shore environments such as coral reefs is challenging due to their high natural biogeochemical variability present over both spatial (m to km) and temporal (diel to seasonal) scales. To make predictions, we must understand the drivers of this variability. The impact of metabolic processes on coral reef biogeochemical variability has been the subject of significant research effort, however, physical factors, including flow speed and light intensity, have received less attention. Here, we measured seawater flow, photosynthetically active radiation (PAR), pH, and DO at three reef habitats (reef flat, lagoon, and outflow channel) in a fringing coral reef system in Okinawa, Japan for 3 weeks in October 2019. During the study, pH ranged from 7.86 to 8.37 units while DO varied from 127 to 369 μmol/kg. Circulation was primarily wave‐driven with mean flow speeds ranging from 14 to 26 cm/s. Flow direction became increasingly consistent at higher flow speeds and traced benthic striations visible in satellite imagery. Multiple linear regression models of daytime changes in pH and DO versus daily mean flow speed and PAR described 25%–74% of the observed variability across all sites while at night, flow speed alone accounted for 7%–75% of the observed variability. These results demonstrate PAR, water flow speed, and the path water takes play important roles in controlling biogeochemical variability within coral reefs and must be considered when assessing their vulnerability to both local and global environmental change. Plain Language Summary: Climate change is causing the ocean to lose oxygen and become more acidic. These changes will likely impact coral reefs but predicting how and when is challenging because coral reefs naturally experience large variations in oxygen and seawater acidity over both space and time. To predict how global changes will impact coral reefs, we must understand the drivers of this natural variability. Past research efforts have explored how much of this variability is caused by biological factors, but fewer efforts have investigated the influence of physical factors such as seawater flow speed and light intensity. In this study, we measured flow speed, light intensity, oxygen concentration, and seawater acid‐base balance at three different habitats on a coral reef for 3 weeks in Okinawa, Japan. Using statistical models, we determined that daily variations in mean flow speed and light intensity accounted for 25%–74% of the variability during the day, and flow speed alone accounted for 7%–75% of the nighttime variability. These results show that flow speed and light intensity play important roles in controlling coral reef oxygen and pH variability and must be considered when assessing how climate change and future changes in seawater chemistry will impact coral reefs. Key Points: Flow speed and light intensity explained 25%–74% of daily and 7%–75% of nightly pH and oxygen variability across different reef habitats Circulation of the Onna‐son coral reef system was driven by waves, but modulated by tides, and was highly consistent Constraining coral reef circulation and light intensity will allow us to better predict future biogeochemical variability on coral reefs